Cuminaldehyde as the Major Component of Cuminum cyminum, a Natural Aldehyde with Inhibitory Effect on Alpha-Synuclein Fibrillation and Cytotoxicity - Morshedi, Dina; Aliakbari, Farhang; Tayaranian-Marvian, Amir; Fassihi, Afshin; Pan-Montojo, Francisco; Pérez-Sánchez, Horacio (Journal of food science, 2015)
Fibrillation of alpha‐synuclein (α‐SN) is a critical process in the pathophysiology of several neurodegenerative diseases, especially Parkinson's disease. Application of bioactive inhibitory compounds from herbal extracts is a potential therapeutic approach for this cytotoxic process. Here, we investigated the inhibitory effects of the Iranian Cuminum cyminum essential oil on the fibrillation of α‐SN. Analysis of different fractions from the total extract identified cuminaldehyde as the active compound involved in the antifibrillation activity. In comparison with baicalein, a well‐known inhibitor of α‐SN fibrillation, cuminaldehyde showed the same activity in some aspects and a different activity on other parameters influencing α‐SN fibrillation. The presence of spermidine, an α‐SN fibrillation inducer, dominantly enforced the inhibitory effects of cuminaldehyde even more intensively than baicalein. Furthermore, the results from experiments using preformed fibrils and monobromobimane‐labeled monomeric protein also suggest that cuminaldehyde prevents α‐SN fibrillation even in the presence of seeds, having no disaggregating impact on the preformed fibrils. Structural studies showed that cuminaldehyde stalls protein assembly into β‐structural fibrils, which might be achieved by the interaction with amine groups through its aldehyde group as a Schiff base reaction. This assumption was supported by FITC labeling efficiency assay. In addition, cytotoxicity assays on PC12 cells showed that cuminaldehyde is a nontoxic compound, treatment with cuminaldehyde throughout α‐SN fibrillation showed no toxic effects on the cells. Taken together, these results show for the first time that the small abundant natural compound, cuminaldehyde, can modulate α‐SN fibrillation. Hence, suggesting that such natural active aldehyde could have potential therapeutic applications.